The reawakening of the sleeping X-ray pulsar XTE J1946+274 - Müller, Sebastian; Kühnel, Matthias; Caballero, I.; Pottschmidt, K.; Fürst, Felix; Kreykenbohm, Ingo; Sagredo, Macarena; Obst, M.; Wilms, Jörn; Ferrigno, C.; Rothschild, R. E.; Staubert, R. (Astronomy & Astrophysics, 2012)
We report on a series of outbursts of the high-mass X-ray binary XTE J1946+274 in 2010/2011 observed with INTEGRAL, RXTE, and Swift. We discuss possible mechanisms resulting in the extraordinary outburst behavior of this source. The X-ray spectra can be described by standard phenomenological models, enhanced by an absorption feature of unknown origin at about 10 keV and a narrow iron K alpha fluorescence line at 6.4 keV, which are variable in flux and pulse phase. We find possible evidence for a cyclotron resonance scattering feature at about 25 keV at the 93% level. The presence of a strong cyclotron line at 35 keV seen in data from the source's 1998 outburst that was confirmed by a reanalysis of these data can be excluded. This result indicates that the cyclotron line feature in XTE J1946+274 is variable between individual outbursts.
Keywords: X-rays: binaries; accretion; accretion disks